2006
DOI: 10.1103/physrevb.74.212403
|View full text |Cite
|
Sign up to set email alerts
|

Quantum phase transition in the heavy-fermion compoundYbIr2Si2

Abstract: We investigate the pressure-temperature phase diagram of YbIr2Si2 by measuring the electrical resistivity ρ(T ). In contrast to the widely investigated YbRh2Si2, YbIr2Si2 is a paramagnetic metal below pc ≃ 8 GPa. Interestingly, a first-order, presumably ferromagnetic, transition develops at pc. Similar magnetic properties were also observed in YbRh2Si2 and YbCu2Si2 at sufficiently high pressures, suggesting a uniform picture for these Yb compounds. The ground state of YbIr2Si2 under pressure can be described b… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
26
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(28 citation statements)
references
References 31 publications
2
26
0
Order By: Relevance
“…As a result, we conclude that the magnetic ordering transition occurs at T M above P c . It is worth noting that P c ($ 1 GPa) is considerably lower than that of other Yb compounds, [3][4][5][6][7] which is an advantage in investigating quantum critical phenomena. We believe that the relatively smaller P c in YbCo 2 Zn 20 is simply due to its proximity to the magnetic QCP at ambient pressure, as inferred from the small T K .…”
Section: -2mentioning
confidence: 99%
See 1 more Smart Citation
“…As a result, we conclude that the magnetic ordering transition occurs at T M above P c . It is worth noting that P c ($ 1 GPa) is considerably lower than that of other Yb compounds, [3][4][5][6][7] which is an advantage in investigating quantum critical phenomena. We believe that the relatively smaller P c in YbCo 2 Zn 20 is simply due to its proximity to the magnetic QCP at ambient pressure, as inferred from the small T K .…”
Section: -2mentioning
confidence: 99%
“…[3][4][5][6][7] The key point here is that Yb ions fluctuate between the nonmagnetic Yb 2þ (J ¼ 0) and the magnetic Yb 3þ (J ¼ 7=2) states. Since the ionic volume of the magnetic Yb 3þ state is smaller than that of the nonmagnetic Yb 2þ one, applying pressure stabilizes the magnetic Yb 3þ configuration and induces the appearance of a magnetically ordered state in contrast to the Ce case.…”
mentioning
confidence: 99%
“…The former is magnetically (presumably AFM) ordered below 0.7 K, whereas the latter is a paramagnet at ambient pressure. Yuan et al (2006) found that by applying pressure the system in its P -type structure undergoes a first-order QPT to an ordered phase at a critical pressure p c ≈ 8 GPa. The nature of the ordered phase is suspected to be FM, but additional investigations are needed.…”
Section: Uranium-based Compoundsmentioning
confidence: 99%
“…4 In other systems evidence is more indirect: FM fluctuations have been shown in YbRh 2 Si 2 5 from transport measurements it was also suggested that the order that appears at high pressure (8 GPa) in YbRh 2 Si 2 and YbIr 2 Si 2 might be FM. 6 Magnetoresistance at high pressures also point to possible FM correlations and order in YbNi 2 Ge 2 .…”
mentioning
confidence: 97%